Pelatihan Literasi Keuangan Digital dan Pencegahan Pinjaman Online Ilegal Bagi UMKM di Desa Campursari - Rahayu, Puji; Srihastuti, Eni (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Financial literacy is an important skill that influences the success of Micro, Small and Medium Enterprises (MSMEs). The aim of the community service program is designed to increase financial literacy among MSMEs in the Campursari village area, Sidorejo District, Magetan Regency. This program involves training on financial planning and preventing illegal online investments and loans. The method used includes lectures. The training participants are MSMEs from various types of businesses in Campursari Village. The results of the training showed an increase in participants' understanding of financial planning, as well as improving practical skills in making financial plans. Training participants also felt an increase in understanding about how to access the OJK website to complain about illegal lending practices or view legal Fintech Lending companies. This program is expected to contribute to the sustainability and growth of MSMEs by increasing financial literacy while preventing illegal loans.